Emotional Intelligence in the Works of Plato - Chatzidimitriou, Efthymia; Triantari, Sotiria (Dia-noesis: A Journal of Philosophy, 2025)
One of the most significant figures in Western philosophy is Plato, who developed the theory of the soul that profoundly influences the understanding of human nature and existence. According to Plato, the tripartite division of the soul consists of the logical (logistikon), the spirited (thymoeides), and the appetitive (epithymetikon), with emotion residing in the spirited part. Since ancient times, the connection between emotion and an individual’s behavior has been evident, as seen in the Delphic maxim "know thyself" and the Platonic assertion that "the whole process of learning has an emotional basis." This work delves into the deep philosophical exploration of the foundations of emotional intelligence through the fundamental Platonic works Republic, Phaedrus, Phaedo, Charmides, Alcibiades, and Gorgias, demonstrating that the tripartite soul and "know thyself" constitute the primary foundation for its subsequent development.